COVID-19 Infection in Pediatric Patients: An Epidemiological Study in Iran - Maryam Naseri; Gholamreza Khademi; Majid Khadem Rezaeian; Shahabaldin Sorouri; Majid Sezavar (Mazandaran University of Medical Sciences, 2022)
Background: COVID-19 is a highly infectious and contagious disease. Since the outbreak of COVID-19, most studies on children have focused on the incidence and prognosis of the disease, and few studies have investigated the epidemiological characteristics of the disease.  Objectives: This study aimed to investigate some epidemiological aspects of the disease in children with COVID-19.  Methods: We examined children with COVID-19 (under 18 years) hospitalized in the North East of Iran from the beginning of the outbreak until the end of September 2020. Study information was collected from patients' medical records and interviews with their parents. We recorded demographic data; history of diseases and taking medicine in children; educational, occupational, and smoking status of parents; patients' residence conditions; and any report of COVID-19 in patients' families and relatives. Results: Of 107 children studied, 57% were male, and 52.3% had no underlying disease. The mean age of patients was 67 months. The Mean±SD weight of the children was 20.36±13.75 kg, and their Mean±SD length of hospital stay was 9±8 days. Multisystem inflammatory syndrome in children (MIS-C) was observed in 34.6% of patients, and its relationship with death was highly significant (P=0.001). The length of hospital stay was influenced by the history of medication consumption (P=0.013) and underlying disease (P=0.001), and its increase was associated with an increased risk of MIS-C (P=0.032) and death (P=0.047). Conclusions: Male sex, length of hospital stay, and MIS-C were identified as risk factors associated with worsening the outcome of COVID-19 disease in children.